CAPITALIZATION RATE ON RESIDENTIAL SECTOR IN MATARAM - Safwira Guna Putra (IQTISHADUNA, 2021)
The capitalization rate is an important factor and must be presented in order to valuing a property applying income approach and direct capitalization method. This paper attempt to measure the capitalization rate on residential sector in district of Mataram through the overall capitalization rate theory developed by the International Association of Assessment Officers. Measurements of central tendency and dispersion were conducted to find out early indications related to the characteristics and tendencies of the capitalization rate. In addition, regressivity and progressivity test was conducted through simple regression analysis and Spearman rank test correlation to determine the lease pattern. Utilizing purposive sampling as many as 70 samples were divided proportionally according to number of sub-district. This research showed that average capitalization rate in district is 4.39%, while average capitalization rate for each sub-district varied widely from 3.7% to 5.31%. Individually, the highest capitalization rate is 6.15% and the lowest is 3.33%. Higher capitalization rate indicated higher percentage return than lower capitalization rate. Regression and correlation analysis showed that capitalization rate tends to regressive against market price or there is a regressive relationship between capitalization rate and market price. The interesting result of this paper is a property with higher market price has lower percentage return than a property with lower market price, and vice versa.